The problem of Presupposition in George Orwell’s Novella Animal Farm - Faizal Risdianto; Noor Malihah; Agung Guritno (State institute of islamic studies salatiga, 2019)
This research attempts to investigate the pragmatics presupposition in George Orwell’s Novella Animal Farm. Specifically, it tries to identify and classify the presupposition used in conversation in Orwell’s novella. The identification is based on the presupposition triggers and classification based on six type of presupposition. The research also attempts to analyze the function in the use of presupposition in conversation. The data in this research are in form of utterances containing presupposition. Based on the classification of six presupposition types according to Yule's theory (1996), 180 presuppositions are found: 69 (38,3%) existential triggered by definite description and possessive construction, 35 (19,4%) lexical triggered by change of state verb; implicative predicate; iterative, 53 (29,4%) structural triggered by WH-question, 4 (2,2%) factive triggered by factive verb/predicate aware glad and 19 (10,6%) non-factive triggered by the verb dream imagine. Based on the six language function by Jakobson (1960), there are 5 functions of presupposition in the novella which are, 57 (47, 9%) referential, 33(27,7%) emotive, 25(21,1%) conative, 3(2,5%) poetic and 1 (0,8%) phatic. In this research, the practice of referential function in applying presupposition is considered as the most frequent.Keywords: Presupposition, presupposition triggers, Novella, George Orwell